Perceived Stress Positively Relates to Insomnia Symptoms: The Moderation of Resilience in Chinese Pregnant Women During COVID-19 - Zou, Hongyu; Tao, Zhen; Zhou, Yongjie; Zhang, Zhiguo; Zhang, Chunyan; Li, Linling; Yang, Jiezhi; Wang, Yanni; Huang, Wei; Wang, Jianhong (Frontiers in Psychiatry, 2022)
Background The government’s COVID-19 pandemic response lockdown strategy had a negative psychological and physical impact on individuals, which necessitated special care to pregnant women’s mental health. There has been no large-scale research on the underlying relationship between perceived stress and insomnia symptoms in pregnant Chinese women up to this point. During the COVID-19 pandemic, we wanted to see if there was an association between perceived stress and insomnia symptoms, as well as the moderating impact of resilience for Chinese pregnant women. Methods This cross-sectional study examined 2115 pregnant women from central and western China using multi-stage sampling methodologies. A systematic questionnaire was used to collect information on sleep quality, perceived stress, and resilience using the Insomnia Severity Index, Perceptual Stress Scale, and Connor and Davidson Resilience Scale. To assess the moderating influence of resilience, hierarchical regressions were used. Results During the COVID-19 pandemic, 18.53% of respondents (N = 2115) reported experiencing sleeplessness. In pregnant women, perceived stress was positively linked with insomnia symptoms (p < 0.001). Furthermore, resilience significantly attenuated the influence of perceived stress on insomnia symptoms in Chinese expectant mother (βinteraction = −0.0126, p < 0.001). Conclusion Pregnant women with strong resilience were less influenced by perceived stress than those with poor resilience. The findings of this study might give empirical proof that health care professionals should identify the relevance of reducing perceived stress in pregnant women with poor resilience and provide better treatment and support when necessary.